Two-Step Sintering of Zirconia Ceramics by Intense High-Energy Electron Beam - Kostenko V. Valeriya; Vasiljev I. P. Ivan Petrovich; Shevelev S. A. Sergey Anatolievich; Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (2019, 2019)
Title screen